2021
DOI: 10.1002/ppul.25578
|View full text |Cite
|
Sign up to set email alerts
|

Reduced pediatric urgent asthma utilization and exacerbations during the COVID‐19 pandemic

Abstract: The COVID‐19 pandemic has had a profound impact on healthcare access and utilization, which could have important implications for children with chronic diseases, including asthma. We sought to evaluate changes in healthcare utilization and outcomes in children with asthma during the COVID‐19 pandemic. We used electronic health records data to evaluate healthcare use and asthma outcomes in 3959 children and adolescents, 5–17 years of age, with a prior diagnosis of asthma who had a history of well‐child visits a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 30 publications
4
39
0
3
Order By: Relevance
“… 18 Similarly, several studies have observed decreases in pediatric exacerbations, hospitalizations, and ED visits among US children with asthma of any severity following the implementation of stay-at-home orders, compared with prior years. 20 , 21 , 23 , 24 Another US report observed 76% fewer ED visits for children with asthma following stay-at-home orders, and a drop in subsequent asthma-related hospital admissions from 31% to 22%. 17 Reduced exacerbation rates have also been reported in Japan, the United Kingdom, and the Netherlands following the implementation of COVID-19 stay-at-home orders in those countries compared with prior-year rates.…”
Section: Discussionmentioning
confidence: 99%
“… 18 Similarly, several studies have observed decreases in pediatric exacerbations, hospitalizations, and ED visits among US children with asthma of any severity following the implementation of stay-at-home orders, compared with prior years. 20 , 21 , 23 , 24 Another US report observed 76% fewer ED visits for children with asthma following stay-at-home orders, and a drop in subsequent asthma-related hospital admissions from 31% to 22%. 17 Reduced exacerbation rates have also been reported in Japan, the United Kingdom, and the Netherlands following the implementation of COVID-19 stay-at-home orders in those countries compared with prior-year rates.…”
Section: Discussionmentioning
confidence: 99%
“…21 Viral infections are the main triggers of asthma exacerbations in all age groups. 13,22 All over the world, there is a growing body of evidence regarding the reduction during the pandemic of health care utilization for asthma, [23][24][25][26][27][28][29][30][31][32][33] and reductions in hospital admissions for seasonal respiratory diseases (upper airway infections, bronchiolitis, and pneumonia) were widely recorded. 3,7,9,10,20,34,35 In addition, the decrease in recorded air pollutants must be considered, because exposure to air pollution is one of the external triggers for the onset of asthma, particularly in larger cities.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] Although SARS-CoV-2 can exacerbate asthma, children admitted to the hospital with asthma and COVID-19 infection did not seem to be at a higher risk of more severe COVID-19 or asthma symptoms than the healthy population. 8,9 The decrease in disease burden was also observed in the outpatient setting where children with asthma consistently required fewer controller medications and oral steroids compared with the prepandemic period. 4,10 Although our center reported fewer ED visits and hospitalization in 2020, the ratio of hospitalization, including to the intensive care unit, to ED visits was higher suggesting that children were more acutely ill at the time of presentation.…”
Section: Introductionmentioning
confidence: 92%